Aural Weather Etude : Installing Atmosphere - Norilo, Vesa; Moreno, Josué (International Computer Music Association, 2021)
The Aural Weather Etude is a collaborative work that explores the spatial dimension as the primary means of organizing music and the devolution of narrative agency to the audience, inspired by the wall drawings by Sol Lewitt. This paper presents the work, the related creative process and some novel computational techniques related to efficient realization of a large number of sound sources in rapid spatial modulation and distance-based amplitude panning.
Keywords: musiikki; äänimaisema; akustiikka